PENGARUH KUALITAS LAYANAN TERHADAP CITRA UNIVERSITAS MUHAMMADIYAH METRO - Oktarina, Dian (Universitas Muhammadiyah Metro Lampung, 2021)
This study aims to determine student responses to student satisfaction and image, how service quality of Universitas Muhammadiyah Metro (UM Metro) affects partially and simultaneously on UM Metro image and the direct effect of UM Metro service quality on image. A total of 314 respondents used as research samples with a sampling technique in the form of proportional random sampling, which was then carried out by processing the data with the help of SPSS software version 25. The results of calculations using multiple regression analysis obtained tangible direct positive effect on UM Metro image. Empathy has a positive direct effect on the image of UM Metro. Responsive has a positive direct effect on the image of UM Metro. Reliability has a positive direct effect on the image of UM Metro. Assurance has a positive direct effect on the image of UM Metro. The results of this study contribute to the service quality and image of UM Metro, the service of lecturers and education staff to students which in turn will have an impact on UM Metro image.Keywords: Image,Â Service Quality (TERRA)